Hubungan Kinerja Petugas Kesehatan Posyandu Lansia Dengan Tingkat Kepuasan Lansia Di Posyandu Lansia Desa Bagu Wilayah Kerja Puskesmas Bagu - Sadam, Lalu Muhammad; Wiguna, Reza Indra; Suhamdani, Haris (Jurnal Kesehatan Qamarul Huda, 2019)
One form of the Puskesmas program which involves the full participation of the community is the "Integrated Service Post" (POSYANDU) Elderly. The Posyandu for the elderly program involves participation in a variety of basic health services for the elderly that are provided specifically to the elderly group. The purpose of this study was to look at the relationship between the performance of health workers in the elderly posyandu with the level of satisfaction of the elderly in the posyandu for the elderly in the village of Bagu. The design of this study used a quantitative design using a cross sectional approach, the sample in this study was the elderly who visited the Posyandu of the elderly in the village of Bagu, a purposive sampling technique, with a total sample of 25 people. There is a strong relationship between nurse performance with the level of satisfaction of the elderly, with a value of p = 0.001, and the level of relationships and strong correlations where rho (?) count: 0.626. There is a strong relationship between cadre performance with the level of satisfaction of the elderly, with a value of p = 0.001, and the level of relationships and strong correlations where rho (?) counts 0.673. Based on the conclusions that have been described in order to carry out further research on the performance of health service officers of the elderly posyandu on the level of satisfaction of the elderly such as nurses and cadres in providing services to the elderly.